Hubungan Anemia dalam Kehamilan dengan Panjang Badan Bayi Baru Lahir di Rumah Sakit Benyamin Guluh Kabupaten Kolaka Tahun 2018 - Kartini, Kartini (Poltekkes Kemenkes Kendari, 2018)
Pregnant women with anemia have disruption in the distribution of oxygen and nutrients from the mother to the placenta and fetus, which affects the function of the placenta. Decreased placental function can result in fetal growth and development disorders. The research objective was to determine the relationship between anemia in pregnancy and body length of newborns at Benyamin Guluh Hospital, Kolaka Regency in 2018. The research design used was case control. The research sample was babies born in 2018, amounting to 84 babies. The data collection instrument was in the form of a filling sheet. Data analysis used chi square test and OR. There were 42 babies (11.73%) who were <48 cm long. There is a correlation between anemia in pregnancy and the length of the baby at Benyamin Guluh Hospital, Kolaka Regency (X2 = 12.5; p = 0.00). Mothers who have anemia have a risk of 5.95 times that their babies have a birth length <48 cm (OR = 5.95; 95% CI = 2.27-15.6).